COVID-19 school closures and mental health of adolescent students: Evidence from rural Mozambique - Chimbutane, Feliciano; Herrera-Almanza, Catalina; Karachiwalla, Naureen; Lauchande, Carlos; Leight, Jessica (International Food Policy Research Institute, 2021)
The onset of the COVID-19 pandemic, entailing widespread school closures as well as acute disruptions to household livelihoods, has presumably had substantial consequences for adolescent well-being in developing country contexts that remain largely unexplored. We present novel evidence about the prevalence of mental health challenges among adolescent students as well as educators in rural Mozambique using data from an in-person survey conducted in 175 schools. In our sample, 31% of students report low levels of well-being (though only 10% suffer from high anxiety): students enrolled in schools that used a wider variety of distance learning measures report lower anxiety, while students reporting familial shocks linked to the pandemic report higher anxiety and lower well-being. Educators experience comparatively lower levels of anxiety and higher well-being, and household-level shocks are most predictive of variation in mental health. However, well-being is negatively affected by the range of hygiene-related measures implemented in schools upon reopening.